Design and development of directional camera mechanism for remotely piloted airship system - Sailan, Nur Nasriq Ellanie (Universiti Sains Malaysia, 2016)
As an important way to obtain the high-resolution remote sensing images, the unmanned aerial vehicle (UAV) play an important role in the area of photogrammetry and remote sensing application. This purpose of this study are to develop the camera platform for remote sensing. The remote sensing are used to monitoring wildlife at Malaysia’s rainforest. The development of camera platform will be used on an Airship. Besides, the camera platform are design based on monitoring requirement. When designing the camera platform the objectives are used as guidelines. Started from preliminary design, then the design are optimized to fulfill the objectives. Finally, optimized design are compared with design in previous studied.